2007
DOI: 10.1002/ejoc.200600879
|View full text |Cite
|
Sign up to set email alerts
|

Mild and Ligand‐Free Palladium‐Catalyzed Cross‐Couplings between Aryl Halides and Arylboronic Acids for the Synthesis of Biaryls and Heterocycle‐Containing Biaryls

Abstract: Ligand‐free palladium‐catalyzed Suzuki–Miyaura cross‐couplings between aryl halides and arylboronic acids performed at room temperature are presented. It was found that both solvent and base had a fundamental influence on the reaction, and the most effective system in terms of yield and rate was observed to be the combination of Pd(OAc)2 with MeONa and alcohols. In the presence of Pd(OAc)2 and MeONa, a variety of aryl halides reacted very rapidly with arylboronic acids in good to excellent yields at room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 51 publications
(22 reference statements)
1
23
0
Order By: Relevance
“…Pd/C-catalyzed hetero-Suzuki-Miyaura coupling between non-heteroaryl halides and heteroarylboronic acids. ) tion in the reactivity (Table 8, entries [1][2][3][4][5], and the use of Na 3 PO 4 ·12 H 2 O could be decreased to 1.0 equiv. (entries 6-10).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pd/C-catalyzed hetero-Suzuki-Miyaura coupling between non-heteroaryl halides and heteroarylboronic acids. ) tion in the reactivity (Table 8, entries [1][2][3][4][5], and the use of Na 3 PO 4 ·12 H 2 O could be decreased to 1.0 equiv. (entries 6-10).…”
Section: Resultsmentioning
confidence: 99%
“…A few ligand-free SuzukiMiyaura coupling reactions of heterocycle-containing substrates catalyzed by a homogeneous palladium catalyst were recently reported. [4,5] Li and co-workers found that the Suzuki-Miyaura couplings between aryl halides and arylboronic acids worked when using the PdA C H T U N G T R E N N U N G (OAc) 2 /NaOMe catalytic system without any ligands and promoters at room temperature, but the protocol required the use of a strong base such as NaOMe, and the coupling between the heteroaryl halides and heteroarylboronic acids was not very efficient. [4] Bryce and co-workers succeeded in the syntheses of functionalized heteroarylpyridines by the Suzuki-Miyaura coupling reactions in the absence of any ligands and additives, but only particularly substituted boronic acids worked well for the smooth reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9a-9d,9f, 12,14] It is noteworthy that the reaction between 2-bromopyridine and o-tolylboronic acid could be conducted in 94 % yield after 60 min (Table 2, entry 3), which is far more efficient than that carried out in an aqueous system.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Effective systems in terms of yield and rate are, for example, Pd(OAc) 2 / Na 2 CO 3 in acetone/H 2 O [37] and Pd(OAc) 2 /MeONa in alcohols. [38] However, the development of mild, rapid, lowcost, and aerobic ligandless-based procedures is still a topic of considerable interest in organic synthesis and industry.…”
Section: Introductionmentioning
confidence: 99%